PERBANDINGAN BIAYA OPERASIONAL SURFACE MINER DAN PENGEBORAN & PELEDAKAN - Handayana, Raden Haris; Pratama, Panji; Lubis, Jihan Farhan; Salahudin, Sani (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2024)
The method of rock breakage is commonly blasting. A few mining companies in Indonesia with facilities near community residences use alternative methods to breaking rock; one of them is using a surface miner. Aspects considered when choosing the method include economic aspects, especially operating costs. In this study case, the size of material that can continue on the next process is ≤ 400 mm; material from surface miner production is at the target; on blasting results, the fragmentation above the target is reduced using a hydraulic breaker; the initiating systems use an electronic detonator (HEBS II) and a non-electric detonator. This difference will affect the cost of the drill and blast. Based on calculated project data, surface miner operating costs are more costly, with an operating cost per ton of USD 1.16 compared with drill and blast methods including hydraulic breaker costs on the initiation system using an electronic detonator (HEBS II) of USD 0.88 per ton and non-electric operating costs of USD 0.83 per ton.